1979
DOI: 10.1007/bf00410648
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation studies of nucleic acid precursors in gastric cancer

Abstract: Measurements of the rate of incorporation of radioactively labeled nucleic acid precursors into the DNA and RNA of gastric carcinoma cell suspensions indicated variable rates of proliferation for the tumors. The rate of incorporation generally correlates to the cytological level of differentiation of the carcinoma. Reduced differentiation of the tumors showed a corresponding increase in the rate of proliferation. Knowing the proliferation-dependent effect of most cytostatica, this results in a resistance to cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1982
1982
1991
1991

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Information eoneerning the expected sensitivity or resistance of individual tumours to cytostatic agents before treatment would be extremely valuable and would enable the 80-90% of patients for whom this form of therapy is unlikely to be effeetive to be spared the likely adverse side effeets. Although sueh predietive studies have been reported to be successful with tumours from a variety of sites , Livingston et al 1980, see also Seetion 3:2:2), a reeent attempt to establish individualized chemotherapy for gastrie carcinoma patients has proved inconclusive (Schlag et al 1979).…”
Section: :4 Gastrointestinal Tractmentioning
confidence: 99%
“…Information eoneerning the expected sensitivity or resistance of individual tumours to cytostatic agents before treatment would be extremely valuable and would enable the 80-90% of patients for whom this form of therapy is unlikely to be effeetive to be spared the likely adverse side effeets. Although sueh predietive studies have been reported to be successful with tumours from a variety of sites , Livingston et al 1980, see also Seetion 3:2:2), a reeent attempt to establish individualized chemotherapy for gastrie carcinoma patients has proved inconclusive (Schlag et al 1979).…”
Section: :4 Gastrointestinal Tractmentioning
confidence: 99%